(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
Fixed costs increased due to the large investment required by modern technology, which has led to an increase in annual depreciation expenses, which is calculated on the basis of the replacement cost and not the historical cost because technologies are constantly changing, machines are constantly changing, and prices change. The paper will also explain how indirect costs in traditional companies have changed into direct costs in high-technology companies. In addition, the most important benefits of nanotechnology, fears of environmental risks and health effects of this technology will be discussed, as well as what proactive methods should be used to ward off these potential dangers to ensure the success of this technology and benefit from it. The research concluded that managers today have become interested in total product costs, both industrial and non-industrial. Traditional cost accounting systems (static cost management methods, such as job order and process costing) provide a static assessment of the profitability of the product because they focus on the process of manufacturing the product. Therefore, it is useful for short-term decisions rather than the long-term. The research concluded that because managers need information about the profitability of their products during all stages of the product’s life, which traditional methods cannot meet because they work to evaluate the products that have a greater contribution to the company’s profits, the role of the dynamic cost management method comes into play (which is represented by the Activity-based system, target cost, Just in time, and product life costs) to evaluate the profitability of the product in order to provide management with information related to the profitability of the product over its life, which makes it a useful basis for making long-term decisions.